2019
DOI: 10.1080/15384101.2019.1671717
|View full text |Cite|
|
Sign up to set email alerts
|

Down-regulated microRNA-183 mediates the Jak/Stat signaling pathway to attenuate hippocampal neuron injury in epilepsy rats by targeting Foxp1

Abstract: Recently, the impacts of microRNAs (miRNAs) have been identified in epilepsy (EP), this study was designed to assess the role of miR-183 in hippocampal neuron injury in EP. Rat EP models were established by injected with lithium-pilocarpine. The pathological observation of rats' hippocampus sections was conducted. Expression of miR-183, Foxp1, Jak1, Stat1, and Stat3 in rats' hippocampal tissues was determined by reverse transcription quantitative polymerase chain reaction (RT-qPCR) and Western blot analysis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…For instance, down-regulating miR-183 inactivates the Jak/Stat signaling pathway by up-regulating Foxp1, thereby strengthening neuronal proliferation and inhibiting apoptosis of hippocampal neurons in epilepsy rats. 36 Additionally, miR-200a silencing protects neural stem cells from OGD/R-induced damage by regulating the STATs/c-Myc and MAPK/c-Myc signaling pathways. 37 Here, we found that STAT1 and NF-κB were up-regulated in the injured cortex of MCAO mice and BV2 cells induced by OGD/R.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, down-regulating miR-183 inactivates the Jak/Stat signaling pathway by up-regulating Foxp1, thereby strengthening neuronal proliferation and inhibiting apoptosis of hippocampal neurons in epilepsy rats. 36 Additionally, miR-200a silencing protects neural stem cells from OGD/R-induced damage by regulating the STATs/c-Myc and MAPK/c-Myc signaling pathways. 37 Here, we found that STAT1 and NF-κB were up-regulated in the injured cortex of MCAO mice and BV2 cells induced by OGD/R.…”
Section: Discussionmentioning
confidence: 99%
“…28 What is more, the level of STAT1 is up-regulated in epilepsy rats' hippocampal tissues. 29 Furthermore, a study observes an increase in STAT1 expression in kidney biopsies with diabetic kidney disease. 30 A new finding of this study was that silenced EZH2 elevated miR-139-5p and decreased STAT1 in HASMCs and arterial tissues of mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, EHZ2 has been observed to be up‐regulated obviously after fluoride exposure 28 . What is more, the level of STAT1 is up‐regulated in epilepsy rats' hippocampal tissues 29 . Furthermore, a study observes an increase in STAT1 expression in kidney biopsies with diabetic kidney disease 30 …”
Section: Discussionmentioning
confidence: 99%
“…Here, we focused on the role of signal transducer and activator of transcription 3 (STAT3) in the adult cerebellum. STAT3 is an essential transcription factor for survival, growth, protection, and metabolic regulation (Murase et al, 2012, Bareyre et al, 2011, Feng et al, 2019, Desai and Harris, 2015. At the behavioral level, STAT3 has a direct impact on multiple animal behaviors, such as running, food-intake, and pain (Mesaros et al, 2008, Herrmann et al, 2008, Fernandes et al, 2015, Buettner et al, 2006, Desai and Harris, 2015, Hu et al, 2020, Guo et al, 2018.…”
Section: Introductionmentioning
confidence: 99%